2018
DOI: 10.3390/atoms6030044
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Electron Density from Stark-Broadened Spectral Lines Appearing in Silver Nanomaterial Plasma

Abstract: This work communicates results from optical emission spectroscopy following laser-induced optical breakdown at or near nanomaterial. Selected atomic lines of silver are evaluated for a consistent determination of electron density. Comparisons are presented with Balmer series hydrogen results. Measurements free of self-absorption effects are of particular interest. For several silver lines, asymmetries are observed in the recorded line profiles. Electron densities of interest range from 0.5 to 3 × 10 17 cm −3 f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
(93 reference statements)
1
2
0
Order By: Relevance
“…The reduction of temperature with time is primarily due to three-body recombination between electrons and ions in the plasma. The values measured were well within the range of LPP temperatures and comparable to other related works published elsewhere 2,15,29,34. In addition, the simulated Saha-LTE spectrum provides relative ion concentrations of different plasma species.…”
supporting
confidence: 88%
“…The reduction of temperature with time is primarily due to three-body recombination between electrons and ions in the plasma. The values measured were well within the range of LPP temperatures and comparable to other related works published elsewhere 2,15,29,34. In addition, the simulated Saha-LTE spectrum provides relative ion concentrations of different plasma species.…”
supporting
confidence: 88%
“…The electron density has been determined by the Stark broadening. 29,39,40 However, other broadenings are not neglected in measuring the electron density.…”
Section: Resultsmentioning
confidence: 99%
“…They proposed the possible reason as recombination from the higher ionic states. In some earlier studies, 8,16 strong spectral asymmetry was reported for the neutral emission. The observed asymmetry was attributed to the presence of a large micro-electric field in the laser produced plasma depending on the time and spatial location within the plasma plume.…”
Section: Introductionmentioning
confidence: 84%